Comportamento hidráulico de um perfil de solo não saturado de Aparecida de Goiânia-GO - BORGES, Camilla Rodrigues (2010)
The hydraulic behavior of a tropical and unsaturated soil profile of Aparecida de Goiânia-GO is presented. The main objective of this research was to contribute to the understanding of hydraulic properties of a tropical soil, with special emphasis on the soil-water characteristic curves and its hysteresis. The research work done was divided into two main parts: physical, chemical and mineralogical characterization; and hydraulic behavior for the unsaturated condition. The characterization tests indicate that the soil profile studied is formed by two horizons. The top layer of 1,50 m comprised of transported material and a bottom layer comprised of young residual soil. The results of particle size analysis have shown that the various sample preparation conditions (i.e., with or without drying, chemical and physical disaggregation) produce different grain-size distribution curves. A varying state of disaggregation can be achieved, that state being dependent on the stability of the soil aggregates. A fairly good correspondence between conventional hydrometer and laser diffraction analysis was achieved, considering supposedly equivalent aggregation conditions. The soil-water characteristic curve (SWCC) was measured for both the natural and the soil reconstituted by mud consolidation. The role played by the soil fabric on the hydraulic behavior of the soil was analyzed. The SWCC was obtained for drying, wetting, and mixed paths, both in terms of total and matric suction. It was determined that the natural and reconstituted soils have distinct SWCCs. The disaggregation achieved with the reconstituted soil results in higher air-entry values and a unimodal SWCC, even when the natural soil presents a bimodal SWCC. Therefore, the pore-size distribution if affected by the different soil structures. The procedure for wetting and drying soil samples used along with the filter paper technique resulted in a number of SWCCs showing absence of hysteresis. The study of the moisture content along the specimen s heights revealed non-homogeneous moisture content distributions, even after 14 day of equilibrium of water potential. It was concluded that it is the very existence of SWCC hysteresis, along with a not sufficiently slow wetting and drying from the specimen surface that results in a non-homogeneous moisture content.